THE “UNKNOWN” GREEK PALEOENVIRONMENT AND FOSSILS: EVALUATING GEOGRAPHY CURRICULUM PROPOSALS FOR ELEMENTARY SCHOOL - Stiliani Fragouli; Αggeliki Rokka; Apostolia Galani (European Journal of Geography)
In this study we introduce teaching proposals to “inject” ammonite fossils, in the Geography syllabus, as evidence of Greek paleoenvironment, which at the moment is the only existing geoscience subject of Greek primary curriculum. Paleontology and mainly fossils attract more and more elementary students and teachers. Unfortunately, in Greece, this trend solely concerns about dinosaurs, despite the fact that the most common Greek fossils are not dinosaurs, but ammonites. Ammonites can be found in large population and diversity inside Greek rocks, as these rocks were part of Tethys΄ seafloor at their geological time. Apart from the informal sources of education, these geoscience/physical geography topics are excluded from elementary national curriculum, thus leaving out the regional paleogeography and geological history practically “unknown” to students and future citizens of our region. Data collected through a pre-test study among the 5 th and 6th grade students confirmed the above belief. A post-test at the original sample, using an open ended questionnaire and students’ drawings, evaluated positively the teaching proposals designed.